The Influence of Work Motivation on Job Performance at the Technical Implementation Unit of Bangun Purba Regional General Hospital - Andrysyah, Andrysyah; Basri, Amin; Sanusi, Asri; Ibrahim, Ibrahim; Oktavianus, Susanto Halim; Zakky, Ahmad Haris (Lembaga Komunikasi dan Informasi Dosen, 2025)
Employee performance has a significant impact on both individual achievement and the overall success of the organization. Motivation is closely related to goal-directed behavior. Employees who consistently perform routine tasks may experience boredom, eventually leading to decreased productivity and performance. At UPT RSUD Bangun Purba, issues such as uneven workload distribution and a lack of initiative among employees have been observed. Additionally, varying levels of employee understanding often lead to miscommunication regarding assigned tasks. This study aims to determine the influence of work motivation on employee performance at UPT RSUD Bangun Purba. This quantitative research was conducted at UPT RSUD Bangun Purba. The population consists of all employees, with a total sample of 30 using total sampling. The study uses both primary and secondary data sourced internally and externally. Data were collected through observation and questionnaires, and analyzed using validity and reliability tests, simple linear regression, partial tests, and the coefficient of determination, with the help of SPSS version 22. The results show that female respondents outnumber male respondents, most are aged 30–41 years, and the majority hold a bachelor’s degree. The analysis meets normality assumptions and shows no heteroscedasticity. The hypothesis test shows that work motivation has a positive and significant effect on employee performance with a t-value of 4.226 2.05183 and significance of 0.000 (p 0.05). The coefficient of determination test shows an R Square value of 48.9%, meaning that work motivation accounts for 48.9% of performance outcomes, while the remaining 51.1% is influenced by other undetected factors.